The teaching work in the Primary School of Minas Gerais state, Brazil: a disciplinary code for an Agent of Modernity - Freitas, Vívian Grasielle Pereira de (2013)
The educational legislation and on the reports and messages of the presidents of Minas Gerais state; Brazil (1906-1927), this paper discusses the monitoring of the teaching work in Primary School. Nevertheless, this analysis comprised, on the one hand, to consider the teaching work as a profession that required a specific code of teachers’ rights and duties; and on the other hand, to recognize that such strategies used by the government intended to make the teacher an agent of modernity. In general, the measures provided by the government tried to ensure the appropriate action of the teacher, prescribed in the discipline programs and legislation of primary school. Thus, in the convergence of different interests, the teacher was subject to different rules and penalties.